Analysis of yield performance and genotype - environment effects on selected maize (Zea mays) landrace accessions of India - WASALA, SAMANTHI K; GULERIA, S K; SEKHAR, J C; MAHAJAN, V; SRINIVASAN, KALYANI; PARSAD, RAJENDER; PRASANNA, B M (The Indian Journal of Agricultural Sciences, 2013)
The study pertains to multi-location phenotypic evaluation of a set of 48 landrace accessions of maize (Zea mays L.)in India. The geographical coordinates of the collection sites of these accessions were first mapped, followed by evaluationof yield performance and flowering behaviour at three locations (Almora, Bajaura and Hyderabad) during 2006â€“07. The study revealed considerable phenotypic diversity among the accessions for grain yield and its components, besides genotype x environment (G Ã— E) interactions. Statistical analyses, including biplot analysis and cluster analysis, demonstrated significant genetic variability among the accessions. Biplot analysis also revealed the potential of some of the landraces to display both location-specific as well as broader adaptability across locations. The study was successful in identifying some highly promising accessions on the basis of their performance for various yield components and flowering behaviour. These include accessions collected from Himachal Pradesh, Madhya Pradesh, Jharkhand, Uttarakhand, Karnataka, Andhra Pradesh, Haryana, Gujarat, Bihar, Orissa and West Bengal. Such accessions could be potentially utilized in developing broad-based gene pools for improving diverse agronomically important traits in maize.